The Business of Mining Mineral Project Valuation - Lilford, Eric; Jones, Odwyn; Chan, Felix (CRC Press/Balkema is, 2018)
Each volume has a discrete focus. This second volume discusses, in some depth, alternative means of assessing the economic viability of mining projects based on the best estimate of the recoverable mineral and/or fossil fuel reserves.